Chronic obstructive lung disease after ammonia inhalation burns: a report of two cases - Insu Kim; Heock Lee; Bo Hyoung Kang; Dong Hyun Lee; Young Hee Nam; Mee Sook Roh; Soo-Jung Um (Kosin Medical Journal, 2022)
Anhydrous ammonia is a commonly used chemical in industry. Ammonia gas inhalation causes thermal injuries and alkali burns in the airway and lung parenchyma. Previous case reports have stated that respiratory sequelae after acute ammonia inhalation burns were associated with structural lung disease, such as bronchiectasis or interstitial lung disease. We herein report two cases of long-term sequelae with persistent airflow limitation after ammonia inhalation burns.